2017
DOI: 10.4274/tjo.28009
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Clinical Signs of Ocular Involvement in Cat Scratch Disease

Abstract: Objectives:To describe ocular manifestations, diagnosis, and treatment of cat scratch disease.Materials and Methods:Clinical records of patients with ocular cat scratch disease were reviewed.Results:Thirteen eyes of 10 patients (7 female, 3 male) with a mean age of 26.9±18.5 years were included. Nine patients had a history of cat contact and had systemic symptoms associated with cat scratch disease 2-90 days prior to the ocular symptoms. Ocular signs were: neuroretinitis in 4 eyes (associated with serous retin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 25 publications
3
24
0
4
Order By: Relevance
“…Furthermore, a recent case series of ocular manifestations of cat-scratch disease reported that 9 of 10 patients had symptoms <3 months before showing development of ocular complications and that 3 patients had been originally given misdiagnoses of etiologies other than cat-scratch disease (31). Given that ocular manifestations of cat-scratch disease were most common in our study, increased diagnoses of atypical cat-scratch disease through March could be a sign of delayed diagnoses, particularly for manifestations that are less severe, such as those involving the eye.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent case series of ocular manifestations of cat-scratch disease reported that 9 of 10 patients had symptoms <3 months before showing development of ocular complications and that 3 patients had been originally given misdiagnoses of etiologies other than cat-scratch disease (31). Given that ocular manifestations of cat-scratch disease were most common in our study, increased diagnoses of atypical cat-scratch disease through March could be a sign of delayed diagnoses, particularly for manifestations that are less severe, such as those involving the eye.…”
Section: Discussionmentioning
confidence: 99%
“…Many ocular manifestations may be related to CSD, with neuroretinitis and focal retinochoroiditis/retinal infiltrates being the most common clinical forms of ocular CSD 1, 5, 6, 7. Conversely, B. henselae is among the most common causes of neuroretinitis 8, 9…”
Section: Introductionmentioning
confidence: 99%
“…One complication of CSD is Parinaud oculoglandular syndrome, which presents with fever, regional lymphadenopathy, and granulomatous follicular conjunctivitis. Other complications include neuroretinitis, focal retinochoroiditis, iridocyclitis, papillitis, peripapillary angiomatosis, serous retinal detachment, branch retinal arteriolar occlusion, endophthalmitis, myelitis, aseptic meningitis, and encephalitis 8,9 . B. henselae is also one of the etiologic agents of bacillary angiomatosis (the other being B. quintana, a humanspecific pathogen with worldwide distribution transmitted by the human body louse Pediculus humanus humanus).…”
Section: Discussionmentioning
confidence: 99%